Dinamika Moderasi Beragama di Rembang Jawa Tengah: Interaksi Nahdlatul Ulama dan LDII dalam Perspektif AGIL - Humam, Abdul Wadud Kasful; Huda, Nur; Alfi, Ahmad Musonnif (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2025)
This study aims to analyze the interactions and responses of the Nahdlatul Ulama (NU) community toward the attitudes of the Indonesian Islamic Da'wah Institute (LDII) by examining the moderation practices implemented by NU figures and the community in Dasun Village, Lasem Sub-district, Rembang, Central Jawa. The research employs a qualitative approach with a field research methodology. The selection of research subjects was conducted using purposive sampling, focusing on informants with in-depth knowledge of NU's moderatism in Dasun Village. The primary subjects include religious and community leaders, village heads, officials, and religious figures affiliated with both NU and LDII, as well as four community members actively engaged in local activities. Data were collected through observation, interviews, and documentation, while data analysis was carried out using data reduction, data presentation, and conclusion drawing. The findings, analyzed through Talcott Parsons' theory of social change, reveal two key aspects. First, the social interactions of NU members reflect positive engagement, which extends beyond mere spatial coexistence to active participation in both social and religious activities. Second, viewed through Parsons' AGIL framework, NU religious and community leaders in Dasun successfully eliminated socio-religious barriers by fostering unity in communal events without emphasizing specific organizational or ideological affiliations. This approach aimed to build solidarity, cohesiveness, and shared responsibility. Furthermore, the integration of religious and community leaders played a crucial role in leveraging social dynamics to mobilize residents toward harmonious coexistence. This was achieved by maintaining togetherness, social cohesion, and latent solidarity, as well as preserving local traditions and cultural practices. These findings contribute to the theoretical discourse on religious moderation and social integration by demonstrating how grassroots leadership fosters harmony in pluralistic communities.